2013
DOI: 10.1128/jvi.00760-13
|View full text |Cite
|
Sign up to set email alerts
|

The PA and HA Gene-Mediated High Viral Load and Intense Innate Immune Response in the Brain Contribute to the High Pathogenicity of H5N1 Avian Influenza Virus in Mallard Ducks

Abstract: Most highly pathogenic avian influenza A viruses cause only mild clinical signs in ducks, serving as an important natural reservoir of influenza A viruses. However, we isolated two H5N1 viruses that are genetically similar but differ greatly in virulence in ducks. A/Chicken/Jiangsu/k0402/2010 (CK10) is highly pathogenic, whereas A/Goose/Jiangsu/k0403/2010 (GS10) is low pathogenic. To determine the genetic basis for the high virulence of CK10 in ducks, we generated a series of single-gene reassortants between C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 58 publications
0
34
1
Order By: Relevance
“…However, Vines et al showed that this single residue has little or no effect on viral replication in ducks (42). Likewise, the PA-I353R mutation in avian H5N1 viruses contributes to viral infection only in mice but not in avian hosts (39,43). Thus, these mutations also seem to be mammal-specific regulators.…”
Section: Figmentioning
confidence: 99%
“…However, Vines et al showed that this single residue has little or no effect on viral replication in ducks (42). Likewise, the PA-I353R mutation in avian H5N1 viruses contributes to viral infection only in mice but not in avian hosts (39,43). Thus, these mutations also seem to be mammal-specific regulators.…”
Section: Figmentioning
confidence: 99%
“…Our team previously isolated a highly pathogenic H5N1 strain that exhibited high virulence in chickens, ducks, mice and guinea-pigs [64] . We have shown that critical amino acids, 101G and 237E in the PA protein, contributed to its high virulence in ducks [120] . Interestingly, the PA gene also accounts for the high virulence of this H5N1 strain in mice and the amino acid 353R acts as the critical molecular marker [51] .…”
Section: Pathogenicity Of Haivsmentioning
confidence: 90%
“…In its natural host, wild waterfowl, infection with the highly pathogenic avian influenza viruses (HPAIVs) generally, leads to minimal or no disease signs [113][114][115] . However, since 2002, accumulating field observations and experimental studies have determined the increased virulence of the currently circulating H5N1 HPAIVs in both waterfowl and wild birds [116][117][118][119][120][121][122][123][124][125][126][127][128][129][130] . Our team previously isolated a highly pathogenic H5N1 strain that exhibited high virulence in chickens, ducks, mice and guinea-pigs [64] .…”
Section: Pathogenicity Of Haivsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, they develop mild or no disease signs upon infection with IAv [6, 104,105]. However, after the long-term evolution, IAv breaks through this virus-host equilibrium and gains the ability to kill their natural host [69][70][71][72][106][107][108][109][110][111][112][113]. Research data from different groups have shown that the PA gene is a key determinant for the lethality of IAv to waterfowl [69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%